2011
DOI: 10.1186/1472-6882-11-108
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity against oral pathogens and immunomodulatory effects and toxicity of geopropolis produced by the stingless bee Melipona fasciculata Smith

Abstract: BackgroundNative bees of the tribe Meliponini produce a distinct kind of propolis called geopropolis. Although many pharmacological activities of propolis have already been demonstrated, little is known about geopropolis, particularly regarding its antimicrobial activity against oral pathogens. The present study aimed at investigating the antimicrobial activity of M. fasciculata geopropolis against oral pathogens, its effects on S. mutans biofilms, and the chemical contents of the extracts. A gel prepared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 60 publications
6
80
0
5
Order By: Relevance
“…Geopropolis has also been proposed as an alternative for prevention and/or treatment of infectious diseases because it has broad antimicrobial activities. In fact, several types of geopropolis have antibacterial properties (Liberio et al 2011, Campos et al 2014.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Geopropolis has also been proposed as an alternative for prevention and/or treatment of infectious diseases because it has broad antimicrobial activities. In fact, several types of geopropolis have antibacterial properties (Liberio et al 2011, Campos et al 2014.…”
Section: Resultsmentioning
confidence: 99%
“…The biological activities and chemical compositions of geopropolis have been reported for many different stingless bee species (Liberio et al 2011, Campos et al 2014. However, there have been no previous pharmacological and chemical analyses of geopropolis from M. mondury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated the biological properties of geopropolis, such as antimicrobial, cytotoxic, antitumor, antioxidant, antinociceptive, antiinflammatory, immunomodulatory, and gastroprotective (Libério et al 2011;Souza et al 2014;Araújo et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Propolis has a complex chemical composition and is mainly composed of resin (50%), wax (30%), essential oils (10%), pollen (5%), and other organic compounds (5%). The application of propolis as a storage media has been studied by many authors [29][30][31]. Propolis has synergistic effect with Dulbecco's modified eagle's medium (DMEM) for the maintenance of cell viability and preservative potential.…”
Section: Propolismentioning
confidence: 99%